The Practice of Buying and Selling Second-hand Clothing from the Perspective of Islamic Economics - Tiara Suci Ramadhani; Nilfatri; Kurniawan (Zabags Qu Publish, 2025)
This study analyzes the practice of buying and selling second-hand clothing at Blok D Market, Geragai District, from the perspective of Islamic economics, focusing on the extent to which such trade conforms to muamalah principles—namely al-ʿadl (justice), ma‘lūm (clarity of the object), prohibition of gharar (uncertainty), and maslahah (public benefit). Employing a qualitative phenomenological approach, the research draws on participant observation, in-depth interviews with vendors and buyers, and market documentation as primary data sources. Findings indicate two predominant transaction modalities: bulk “sack” purchases (sack) and retail sales; the former carries a higher risk of gharar because buyers cannot inspect goods prior to purchase, while the latter more readily satisfies clarity and justice principles by allowing buyers khiyar (choice) and inspection. Vendors mitigate uncertainty through systematic sorting, cleaning, and tiered pricing, thereby preserving market trust and ethical conduct aligned with Islamic values. The study contributes empirical evidence linking classical muamalah concepts to informal market practices and offers a foundation for context-sensitive guidance and policy interventions that enhance the ethical, equitable, and sustainable governance of second-hand clothing trade.